The prophylactic effect of Lactobacillus rhamnosus GG on incidence of acute rotavirus diarrhea in children: a systematic review randomized double-blind placebo-controlled trials - Elaheh Ahmadi; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2014)
Background: Rotavirus is one of the most common etiologic agent of severe acute diarrhea in infants and children which results in high mortality and morbidity globally. Prophylactic strategies are required to prevent acute rotavirus diarrhea. Recently, the beneficial effect of probiotic therapy in control of rotavirus diarrhea was noted in many investigations. This systematic review investigated the prophylactic effect of Lactobacillus rhamnosus GG on the incidence of acute rotavirus diarrhea in infants and children. Methods: Databases including PubMed, Cochrane Controlled Trial Register (CCTR), Google Scholar, Science direct and Ovid (Wolters Kluwer health) were searched for articles and reviews from 1980-2013. Reviewers selected randomized clinical trials that met the study inclusion criteria. The outcome measures included incidence of rotavirus diarrhea, duration of diarrhea, and hospital stay. Results: The search results included three trials with 1043 eligible patients. The results indicated that the use of Lactobacillus rhamnosus GG compared with placebo significantly affected the incidence of rotavirus diarrhea without influencing the duration of hospital stay. Conclusion: Some studies signified the role of Lactobacillus rhamnosus GG in preventing acute rotavirus diarrhea however we did not find sufficient trials with certain method to evaluate this influence.